Exportaç\~oes e inovaç\~ao: Uma análise para América Latina e Sul-Sudeste da Ásia - Marcelo José Braga Nonnenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper intends to compare the technological intensity of Latin American and South-Southeast exports in the last three decades. In this period exports from Asian countries increased at a much higher speed than the one observed in Latin American countries. The main reason was the higher and increasing ratio of high-tech goods in Asian exports. The main contribution of this article is to build an indicator of technological intensity that allows to adequately measure the knowledge content of exports. This indicator has been calculated for all countries in the present sample for the period 1983-2008, based on COMTRADE-WITS data. The results show that Asian technological intensity is greater than that for Latin American countries. It has also been correlated to the exports growth rate for 1983-2000 and 2001-2008. In the first period, there is a positive relation between the two variables, with China and Hong Kong as outliers. This relation becomes negative in the second period thanks to the dramatic increase in commodities prices.
Keywords: F14; 330